Litotes in Paul: Not an Insignificant Trope - Croy, N. Clayton (Novum Testamentum, 2024)
It is sometimes claimed that litotes, the rhetorical trope in which the negation of the contrary is asserted, is largely limited in the New Testament to the Acts of the Apostles, and Paul does not commonly use it. But in fact Paul does use it and with greater sophistication and complexity than Luke. This article reviews the ancient rhetorical handbooks and scholia with respect to litotes, surveys its various functions, and then demonstrates that Paul uses it frequently and deftly as a rhetorical technique of restraint to enhance his credibility.